Diversity of nitrogen-fixing rhizobacteria associated with sugarcane: a comprehensive study of plant-microbe interactions for growth enhancement in Saccharum spp - Singh, Rajesh Kumar; Singh, Pratiksha; Li, Hai-Bi; Song, Qi-Qi; Guo, Dao-Jun; Solanki, Manoj K.; Verma, Krishan K.; Malviya, Mukesh K.; Song, Xiu-Peng; Lakshmanan, Prakash; Yang, Li-Tao; Li, Yang-Rui (BMC plant biology, 2020)
Nitrogen is an essential element for sugarcane growth and development and is generally applied in the form of urea often much more than at recommended rates, causing serious soil degradation, particularly soil acidification, as well as groundwater and air pollution. In spite of the importance of nitrogen for plant growth, fewer reports are available to understand the application and biological role of N fixing bacteria to improve N nutrition in the sugarcane plant. In this study, a total of 350 different bacterial strains were isolated from rhizospheric soil samples of the sugarcane plants. Out of these, 22 isolates were selected based on plant growth promotion traits, biocontrol, and nitrogenase activity. The presence and activity of the nifH gene and the ability of nitrogen-fixation proved that all 22 selected strains have the ability to fix nitrogen. These strains were used to perform 16S rRNA and rpoB genes for their identification. The resulted amplicons were sequenced and phylogenetic analysis was constructed. Among the screened strains for nitrogen fixation, CY5 (Bacillus megaterium) and CA1 (Bacillus mycoides) were the most prominent. These two strains were examined for functional diversity using Biolog phenotyping, which confirmed the consumption of diverse carbon and nitrogen sources and tolerance to low pH and osmotic stress. The inoculated bacterial strains colonized the sugarcane rhizosphere successfully and were mostly located in root and leaf. The expression of the nifH gene in both sugarcane varieties (GT11 and GXB9) inoculated with CY5 and CA1 was confirmed. The gene expression studies showed enhanced expression of genes of various enzymes such as catalase, phenylalanine-ammonia-lyase, superoxide dismutase, chitinase and glucanase in bacterial-inoculated sugarcane plants. The results showed that a substantial number of Bacillus isolates have N-fixation and biocontrol property against two sugarcane pathogens Sporisorium scitamineum and Ceratocystis paradoxa. The increased activity of genes controlling free radical metabolism may at least in part accounts for the increased tolerance to pathogens. Nitrogen-fixation was confirmed in sugarcane inoculated with B. megaterium and B. mycoides strains using N-balance and N isotope dilution in different plant parts of sugarcane. This is the first report of Bacillus mycoides as a nitrogen-fixing rhizobacterium in sugarcane.